PENGARUH BULLYING DALAM KOMUNIKASI INTERNAL TERHADAP KINERJA KARYAWAN DI PERUSAHAAN WISATA - Henni Gusfa (MediaKom : Jurnal Ilmiah Komunikasi, 2016)
Abstract: Communication within an organization is very basic, but bad communication can damage the existingcultural order within an organization. Poor communication can cause bullying and have an impact on employeeproductivity. This study aims to determine how much influence bullying in internal communication onperformance employee.Paradigm of research is positivistic and research method used is survey with quantitative approach. Dataanalysis method used is multiple linear regression. Furthermore, the object of his research is the employee ofthe South Jakarta Tourist Company, amounting to 55 employees taken with a sampling census. Result of t testcalculation, the influence of internal communication (X1) on performance employee (Y) obtained count valuetcount 4,707> 2,007 ttable with significance value 0.000 <0.005. The results of these calculations indicate thatinternal communication variables significantly affect the performance employee.Calculation with t test on variable bullying (X2), obtained tcount of 3,680> 2.007 table with significance value0.001 <0.005. The results show that the variables of internal communication significantly affect the employeeperformance. Next with the F test, the Fcount value is 86.043 with a significance level of 0.000. It means thatHO is rejected and Ha is accepted, since the value of Fcount is 86.043> 3.18 (Ftabel) and the significancevalue is 0.000 <0.05. So that can be stated internal communication and bullying effect simultaneously toperformance employee. The magnitude of influence on the basis of the coefficient of determination of the twoindependent variables to the dependent variable is 0.768 or 76.8%. While the remaining 23.2% influenced byother variables that are not described in this study. Keywords: internal communication, bullying, employee performance